World Development Report 2022 : Finance for an Equitable Recovery - World Bank (Washington, DC: World Bank, 2022)
World Development Report 2022: Finance for an Equitable Recovery examines the central role of finance in the economic recovery from COVID-19. Based on an in-depth look at the consequences of the crisis most likely to affect low- and middle-income economies, it advocates a set of policies and measures to mitigate the interconnected economic risks stemming from the pandemic—risks that may become more acute as stimulus measures are withdrawn at both the domestic and global levels. Those policies include the efficient and transparent management of nonperforming loans to mitigate threats to financial stability, insolvency reforms to allow for the orderly reduction of unsustainable debts, innovations in risk management and lending models to ensure continued access to credit for households and businesses, and improvements in sovereign debt management to preserve the ability of governments to support an equitable recovery.